Perception of e-business adoption in agribusiness MSMEs. Issue 1 (July 2021) - Khomah, I; Rahayu, E S; Handayani, S M
Abstract: Climate change is unavoidable due to global warming and will have a broad impact on every aspect of life, including agriculture. This poses a significant threat to the agricultural sector. Furthermore, it raises new problems of the sustainability of food production and agricultural production systems in general. This has an indirect impact on agribusiness MSME, particularly in terms of the availability of food for raw materials for MSME products. Furthermore, agribusiness MSMEs should be competitive to face the global market. As a consequence, they should embrace innovations that support business activities in the current era of the Industrial Revolution 4.0. Using e-business in their business practices is one of the efforts that agribusiness MSMEs can make. E-business is a type of internet-based business practice that can help improve the efficiency of various business processes. This research aims to determine the perceptions and levels of e-business adoption among agribusiness MSMEs in Sukoharjo Regency. The survey method was used in this study, along with the purposive sampling technique. A questionnaire was used to gather data from 252 agribusiness MSMEs in Sukoharjo. An in-depth interview was used to identify the research variable indicators more thoroughly. The results reveal that the frequency of e-business use by MSME actors in Sukoharjo Regency remains low. However, MSME actors have a positive perception of the benefits of using e-business. Therefore, there is a great opportunity for the future implementation of e-business.